Comparison of Marginal Fit and Fracture Strength Between Conventional and CAD/CAM-Milled Provisional Crowns: A Systematic Review - Puppala, Padmapriya; Mistry, Gaurang S.; Parab, Sheetal B.; Chitnis, Ankita V.; Pokharkar, Amit B.; Shetty, Krsna (Journal of Neonatal Surgery, 2026)
The present systematic review aimed to evaluate and compare the marginal fit and fracture strength of provisional crowns between conventional techniques and CAD/CAM milling technology. A comprehensive literature search was conducted across databases including PubMed, Scopus, Web of Science, and the Cochrane Library for studies published between January 2000 and June 2023. After screening 743 records, 12 studies met the inclusion criteria and were included in the final qualitative synthesis. The findings consistently demonstrated that CAD/CAM-milled provisional crowns offer improved marginal adaptation and enhanced fracture resistance compared to conventionally fabricated crowns, with low heterogeneity (I² = 0.48%). Limitations include methodological variability and lack of in vivo studies assessing long-term outcomes and patient satisfaction. Further clinical research is recommended to validate these findings across diverse populations and settings. CAD/CAM technology appears to be a promising and efficient alternative for producing high-quality provisional restorations in contemporary prosthodontics.